Prevajanje skatološkega besedišča in erotične književnosti - Fritz, Ervin (Hieronymus, 2025)
The author of this contribution sets out to understand how the Slovenian nation, despite its long and storied history, appears strikingly devoid of profanities and largely lacks its own bawdy folk poetry. In particular, it attempts to establish what factors may have contributed to its continued existence in this context of pious restraint. He concludes with somewhat reluctant reflections on how this shapes both the writing and the translation of more erotically-charged texts.